Overcoming sexual addiction: peculiarity, dynamics of development, consequences and therapy - Kurlak, Iryna (Forum Pedagogiczne, 2019)
The goal of this article is to show the peculiarity of sexual addiction – a manifestation of behavioral addiction – characteristics, specificity, dynamics of development, degrees of sex addiction, negative consequences for a person and her or his environment, families and relatives, and forms of therapy.